2018
DOI: 10.1016/j.midw.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Recency of migration, region of origin and women's experience of maternity care in England: Evidence from a large cross-sectional survey

Abstract: BackgroundIn the UK, changes to legislation in 2003 regarding the free movement of people in the European Union resulted in an increase in immigration from countries that joined the EU since 2004, the Accession countries.ObjectiveTo describe and compare the maternity experiences of recent migrant mothers to those who had been resident in the UK for longer, and to UK-born women, while taking into account their region of origin.DesignCross-sectional national survey.SettingEngland, 2009.ParticipantsRandom sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 30 publications
(38 reference statements)
2
24
1
Order By: Relevance
“…Mother’s country of birth may influence birth outcomes of infants through conditions and risk factors which may be common to migrant groups, for example, health behaviour, cultural, environmental, economical, social and lifestyle factors,26 and experiences of migration. The finding of health advantages among migrant populations relative to native populations may be considered an epidemiological paradox,27 in view of the possible socioeconomic disadvantages28 and poorer experience of health care29 of the former. A number of potentially complementary factors may explain this paradox,30 including: health selection among some immigrant groups, including the ‘healthy worker’ effect by which healthier, better educated individuals are more likely to successfully migrate in search of work;31 healthier lifestyles among immigrants from some societies (‘cultural buffering’) including lower prevalence of smoking,32 alcohol consumption33 and obesity and immigration policies at destination which may profile and select immigrants on the basis of their health status 34.…”
Section: Discussionmentioning
confidence: 99%
“…Mother’s country of birth may influence birth outcomes of infants through conditions and risk factors which may be common to migrant groups, for example, health behaviour, cultural, environmental, economical, social and lifestyle factors,26 and experiences of migration. The finding of health advantages among migrant populations relative to native populations may be considered an epidemiological paradox,27 in view of the possible socioeconomic disadvantages28 and poorer experience of health care29 of the former. A number of potentially complementary factors may explain this paradox,30 including: health selection among some immigrant groups, including the ‘healthy worker’ effect by which healthier, better educated individuals are more likely to successfully migrate in search of work;31 healthier lifestyles among immigrants from some societies (‘cultural buffering’) including lower prevalence of smoking,32 alcohol consumption33 and obesity and immigration policies at destination which may profile and select immigrants on the basis of their health status 34.…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to access for other groups have also been identified across the care pathway – for example, ethnic and socio‐economic differences in initial identification by universal services 185 , and socio‐economic differences in access to inpatient mother and baby units 186 . Qualitative research finds that different professional groups use different languages to communicate risk and have different perspectives of mental illness severity.…”
Section: Service Deliverymentioning
confidence: 99%
“…Five studies approached three dimensions of involvement [57][58][59][60][61], and none addressed all of them. Evidence derives mainly from studies conducted in the UK (n = 8), Australia (n = 3) and Portugal (n = 3) and published between 2001 [62,63] and 2018 [64,65], with an increase of research in recent years. A total of 14 out of the 22 studies reviewed were published between 2013 and 2018.…”
Section: Migrant and Ethnic Minority Involvement In Maternal Carementioning
confidence: 99%
“…Two population-based studies carried out in England found Black and Minority Ethnic women to be less likely to be spoken to in a way that they could understand [59] and to rate communication with maternal care staff worse than native women [61]. Suboptimal communication was also more often reported by migrant women than by non-migrant women in studies undertaken in France, Sweden and England [64,72,73].…”
Section: Communicationmentioning
confidence: 99%